-19-(-13)=

Simple and best practice solution for -19-(-13)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -19-(-13)= equation:


-19-(-13)=0

We simplify the equation to the form, which is simple to understand
-19-(-13)=0

Remove unnecessary parentheses
-19+13=0

We move all terms containing to the left and all other terms to the right.
0=0+19-13

We simplify left and right side of the equation.
0=+6

0=6

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| -4x+2(3x-1)-12=0 | | 6x+7(x+17)=184 | | -28+11= | | -1x+7=1-3x | | 2x+46=17+5x | | -7x-3(-4x+13)=11 | | -34+43= | | 7/8(3/5) | | y=-(x^2+4x-9) | | 7x-(3x-6)-2=20 | | 9x^2+18x-40x=0 | | v-8=16+4v | | 25x-(6x-12)= | | 7m-5m+3m-3m=46 | | 3(n+2)+(n*0.5)=2(n+1)-14 | | 18-6u= | | 34-(34)= | | 7g+14+-5g=-8 | | 4r-r-3r+r=11 | | -8w=-144 | | (34+11)+9=(11+34)+9 | | 5x-2(-x-11)=78 | | 10p-2(3p-6)=4(5p-6)10p | | x^3-6x^2-12x=0 | | 2x+10000=497500 | | 2.4x+11.3=3.7-0.6x | | 3/4x-12=1/4x-9 | | 0.3x+-0.2x=2 | | -9(7)= | | 32x^2/990^2 | | 164=6x-4(-4x+3) | | x^3-5x^2-12x=0 |

Equations solver categories